Compliance in contributions payment: Fiscal authorities versus religious authorities in Mexico - Chávez Maza, Luis Augusto; Elbittar, Alexander; Hernández Trillo, Fausto (Estudios Económicos de El Colegio de México, 2015)
This paper studies fiscal correspondence and fiscal trust. Through an experimental design carried out in Oaxaca, Mexico it explores which authority, the religious or the civil one, is better at collecting contributions to finance common goods. Results suggest that fiscal correspondence is the main factor to explain better collection. That is, when the good is observable, people are more willing to pay the contribution.